New Di- and Triorganotin(IV) Tyrosylalaninates as Models for Metal—Protein Interactions: Synthesis, Structural Characterization, and Potentiometric Studies of Tyrosylalanine, Glycyltyrosine, and Glycylisoleucine with Di- and Trimethyltin(IV) Moieties in Aqueous Medium. (15th March 2012) - Nath, Mala; Sulaxna,; Song, Xueqing; Eng, George
Abstract : Di- and triorganotin(IV) derivatives of tyrosylalanine (H2 Tyr-Ala) with general formula R2 Sn(Tyr-Ala) (where R = Me, n -Bu, n -Oct, and Ph) and R3 Sn(HTyr-Ala) (where R = Me and Ph) have been synthesized and structurally characterized in the solid state as well as in solution on the basis of various spectroscopic techniques, namely. FT-IR, multinuclear ( 1 H, 13 C and 119 Sn) NMR and 119 Sn Mössbauer. These investigations suggest that tyrosylalanine in R2 Sn(Tyr-Ala) acts as dianionic tridentate ligand coordinating through carboxylate oxygen [–C(O)O − ], amino (–NH2 ), and (CO)N peptide - nitrogen, while in the case of R3 Sn(HTyr-Ala), the ligand acts as monoanionic bidentate coordinating through –C(O)O − and –NH2, and the polyhedron around tin in R2 Sn(Tyr-Ala) and R3 Sn(HTyr-Ala) is a distorted trigonal-bipyramidal. Equilibrium (pH-metric) studies of the interaction of Me2 Sn(IV) 2+ and Me3 Sn(IV) + with dipeptides namely, tyrosylalanine (H2 Tyr-Ala), glycyltyrosine (H2 Gly-Tyr), and glycylisoleucine (H2 Gly-Ile), in aqueous solution ( I = 0.1 M KNO3, 298 K) have also been carried out. The concentration distribution of the various complex species in solution has been evaluated as a function of pH. It has been found that in these dipeptides, [–C(O)O −, N −, NH2 ] coordinated complexes are dominant in the neutral pH range with a trigonal-bipyramidal structure. The complex species formed are water soluble in the pH range 2.7–10.5. In all of the studied systems, no polymeric species have been detected in the experimental pH range. Beyond pH 8.0, significant amounts of hydroxo species, namely. Me3 Sn(OH) and Me2 Sn(OH)2, are formed.